Preparation of extremely active ethylene tetramerization catalyst [iPrN(PAr2)2 −CrCl2]+ [B(C6 F5)4]– (Ar = −C6H4-p-SiR3) - Lee, Jung Hyun; Baek, Jun Won; Lee, Dong Geun; Ko, Ji Hyeong; Lee, Dong Geun; Cho, Kye Sung; Lee, Jin Woo; Lee, Bun Yeoul (Catalysts, 2021)
Numerous efforts have been made to achieve “on-purpose” 1-octene production since Sasol discovered a Cr-based selective ethylene tetramerization catalyst in the early 2000s. By preparing a series of bis(phosphine) ligands iPrN(PAr2)2 where the Ar contains a bulky –SiR3 substituent (Ar = −C6 H4-p-Si(nBu)3 (1), −C6 H4-p-Si(1-hexyl)3 (2), −C6 H4-p-Si(1-octyl)3 (3), −C6 H4-p-Si(2-ethylhexyl)3 (4), −C6 H4-p-Si(3,7-dimethyloctyl)3 (5)), we obtained an extremely active catalyst that meets the criteria for commercial utilization. The Cr complexes [iPrN(PAr2)2 −CrCl2 ]+ [B(C6 F5)4 ]–, obtained by reacting ligands 1–5 with [(CH3 CN)4 CrCl2 ]+ [B(C6 F5)4 ]–, showed high activity exceeding 6000 kg/g-Cr/h, when combined with the inexpensive iBu3 Al, thus avoiding the use of expensive modified methylaluminoxane (MMAO). The bulky –SiR3 substituents played a key role in the suc-cess of catalysis by blocking the formation of inactive species (Cr complexes coordinated by two iPrN(PAr2)2 ligands, that is, [(iPrN(PAr2)2)2 −CrCl2 ]+ [B(C6 F5)4 ]–). Among the complexes prepared, [3−CrCl2 ]+ [B(C6 F5)4 ]– exhibited the highest activity (11,100 kg/g-Cr/h, 100 kg/g-catalyst) with high 1-octene selectivity (75 wt%) and, moreover, mitigated the generation of undesired > C10 fractions (10.7 wt%). A 10-g-scale synthesis of 3 was developed, as well as a facile and low-cost synthetic method for [(CH3 CN)4 CrCl2 ]+ [B(C6 F5)4 ]– .
Keywords: 1-octene production; Bis(phosphine) ligand; Chromium catalyst; Ethylene tetramerization; Tetrakis(pentafluorophenyl)borate